(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
One characteristic of the Italian DNA database derives from the legislative choice to create a specific subset of genetic profiles, with the purpose of identifying missing persons, corpses and unidentified human remains kept for some time in forensic institutes without being associated with a name. In this case the technology enables the identification of unknown corpses and human remains, allowing relatives to give homage to their loved ones.